Human Lysyl Oxidase Over-Expression Enhances Baseline Cardiac Oxidative Stress but Does Not Aggravate ROS Generation or Infarct Size Following Myocardial Ischemia-Reperfusion - Laura Valls-Lacalle; Lídia Puertas-Umbert; Saray Varona; José Martínez-González; Cristina Rodríguez; Antonio Rodríguez-Sinovas (MDPI AG, 2021)
Lysyl oxidase (LOX) is an enzyme critically involved in collagen maturation, whose activity releases H2O2 as a by-product. Previous studies demonstrated that LOX over-expression enhances reactive oxygen species (ROS) production and exacerbates cardiac remodeling induced by pressure overload. However, whether LOX influences acute myocardial infarction and post-infarct left ventricular remodeling and the contribution of LOX to myocardial oxidative stress following ischemia-reperfusion have not been analyzed. Isolated hearts from transgenic mice over-expressing human LOX in the heart (TgLOX) and wild-type (WT) littermates were subjected to global ischemia and reperfusion. Although under basal conditions LOX transgenesis is associated with higher cardiac superoxide levels than WT mice, no differences in ROS production were detected in ischemic hearts and a comparable acute ischemia-reperfusion injury was observed (infarct size: 56.24 ± 9.44 vs. 48.63 ± 2.99% of cardiac weight in WT and TgLOX, respectively). Further, similar changes in cardiac dimensions and function were observed in TgLOX and WT mice 28 days after myocardial infarction induced by transient left anterior descending (LAD) coronary artery occlusion, and no differences in scar area were detected (20.29 ± 3.10 vs. 21.83 ± 2.83% of left ventricle). Our data evidence that, although LOX transgenesis induces baseline myocardial oxidative stress, neither ROS production, infarct size, nor post-infarction cardiac remodeling were exacerbated following myocardial ischemia-reperfusion.